Clinicopathological appraisal of cutaneous cysts: A 2-year retrospective observational study - Geeti Khullar; Mithilesh Chandra (Wolters Kluwer Medknow Publications, 2023)
Background: Cysts, primarily epidermal and trichilemmal, are commonly seen in clinical practice. Rupture, infection, inflammation, and rarely malignant transformation may complicate the cysts. This study aims to analyze the clinicohistological features of cutaneous cysts. Materials and Methods: A retrospective review of patients with the diagnosis of cyst confirmed on histopathology over the past two years (2020-2021) was performed. Clinical details comprised of age, gender, site of involvement, size, duration, and associated symptoms. Histological examination included cyst wall lining, type of keratinization, complications like rupture, inflammation, foreign body giant cell reaction, calcification, and malignant change. Results: A total of 324 cases with mean age of 37.9 years and equal gender distribution were identified. Most frequent diagnosis was epidermal cyst in 89.8%, followed by trichilemmal cyst in 8.9% of cases. Rare types included follicular hybrid cyst, verrucous cyst, vellus hair cyst, and steatocystoma. Most common complication was cyst rupture in 54.3% of epidermal cysts. Proliferating epidermal and proliferating trichilemmal cysts were noted in one and two cases, respectively. Two cases revealed malignancy arising in the wall of epidermal cyst. Limitations: The retrospective study design and non-availability of follow-up data, especially for proliferating cysts and cysts with malignant transformation were the main limitations of this study. Conclusion: Histopathologic examination of excised cutaneous cysts is paramount in reaching accurate diagnosis of the type of cyst and associated secondary changes to enable appropriate management.